STRATEGI PENGEMBANGAN APLIKASI PADA PENATAUSAHAAN DAN PERTANGGUNGJAWABAN DALAM AKUNTABILITAS PELAKSANAAN ANGGARAN PENDAPATAN BELANJA DAERAH - Beben, Machbuba; Hardian, Dafyar Eliadi; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze application development strategies to support regional financial administration and accountability in order to improve accountability in the implementation of the Regional Revenue and Expenditure Budget (APBD) at the Tangerang City Regional Financial Management Agency (BPKD). The research problem focuses on how application implementation can address the challenges of transparency, effectiveness, and efficiency in regional financial management. The research method used a descriptive qualitative approach, with data collection techniques through interviews, observations, and document reviews. Data analysis was conducted using the SWOT (Strengths, Weaknesses, Opportunities, Threats) theoretical framework and reinforced by Albert S. Humbyres's perspective on strategic alignment, which emphasizes the importance of alignment between internal organizational factors and external dynamics for effective development strategies. The results indicate that regional financial management applications have made a positive contribution to strengthening transparency and accelerating administrative processes, although obstacles remain such as limited human resources, the need for technological infrastructure improvements, and resistance to adapting to new systems. Opportunities can be maximized through collaboration between regional agencies and the utilization of information technology developments, while external threats can be minimized by strengthening data security policies and risk management. The research conclusions confirm that the development of regional financial administration and accountability applications plays a crucial role in improving the accountability of regional budget management. Recommendations include the need for a strategy to improve staff competency, continuous technology upgrades, and strengthening cross-sectoral regulations and coordination. Keywords: Application Development Strategy, Accountability, SWOT Theory, BPKD.